Analisis Perilaku Sosial Masyarakat Kampung Tegalmas Jogonalan Klaten dalam Tradisi Yasinan dan Tahlilan : (Study Deskriptif Melalui Pendekatan Teori Pertukaran Sosial) - Muhamad Nur Zaman (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2026)
This article describes the social behavior of the people of Tegalmas Village, Jogonalan, Klaten, in the traditions of Yasinan and Tahlilan using the Social Exchange Theory approach. Social Exchange Theory is a part of interpersonal communication theory that explains how individuals enter into and maintain social interactions by considering the consequences obtained from such interpersonal relationships. The theory assumes that individuals evaluate the rewards and costs of social interactions before deciding whether to continue or terminate a relationship. In the context of Yasinan and Tahlilan traditions, community participation is influenced by the perceived benefits and social values gained through these activities. The findings indicate that positive relationships characterized by social solidarity, mutual assistance, and religious values encourage community members to maintain their involvement in these traditions. Conversely, when the perceived costs outweigh the benefits, participation tends to decrease. Social Exchange Theory predicts that the value of a relationship influences its outcome, determining whether individuals will continue or discontinue their involvement. Positive relationships are generally expected to endure, whereas negative relationships are more likely to end.